Perinatal Factors Associated with Spontaneous Regression of Retinopathy of Prematurity One Year Experience from a Tertiary Care Hospital - P KUMAR; K S KUMARAVEL; D SATHEESHKUMAR; S GOBINATHAN; P SAMPATHKUMAR; K VELMURUGAN (JCDR Research and Publications Pvt. Ltd., 2020)
Introduction: Spontaneous regression of Retinopathy of Prematurity (ROP) usually happens without serious residual sequelae in most neonates, while in some, blindness or serious visual impairment results from severe ROP. Aim: The aim of the study was to estimate the incidences of ROP that spontaneously regress and ROP that requires intervention and to identify the perinatal factors that are associated with spontaneous regression of ROP. Materials and Methods: This is a one year prospective descriptive study done in the Special Newborn Care Unit of a tertiary care hospital. All neonates diagnosed to have ROP of any stage on screening were included in the study. All these neonates were followed-up weekly for progression or regression of ROP. Data collected from case records included demographic, perinatal and neonatal profile of the study participants. The study group was divided into two groups - those neonates with spontaneous regression of ROP (Group 1) and those neonates who had severe ROP requiring intervention (Group 2). Results: The incidence of ROP was 22.89%. The incidences of ROP spontaneously regressing and ROP requiring intervention were 93.5% and 6.5%, respectively. The univariate analysis of the factors showed a positive Odds Ratio (OR) for spontaneous regression for male gender, multiparity, lower segment caesarian section delivery and increasing gestational age. The OR was negative for factors like maternal anaemia, neonatal Respiratory Distress Syndrome (RDS), neonatal sepsis, phototherapy usage, neonatal blood transfusion, neonatal Intraventricular Hemorrhage (IVH) and increasing oxygen days. The Chi-square test revealed a significant p-value (<0.05) for the factors including IVH (p=0.002), gestational age (p=0.01), birth weight (p=0.01) and oxygen days (p=0.003). Conclusion: The present study reiterates the need to develop a statistical model or a scoring system to predict the need for intervention in neonates with ROP by doing a larger multicentric study